High GTSE1 expression promotes cell proliferation, metastasis and cisplatin resistance in ccRCC and is associated with immune infiltrates and poor prognosis - Lei, Pu; Zhang, Mengzhao; Li, Yan; Wang, Ziming (Frontiers in Genetics, 2023)
Background: Clear cell renal cell carcinoma (ccRCC) is the most common and fatal form of kidney cancer, accounting for 80% of new cases. Although it has been reported that GTSE1 is highly expressed in a variety of tumors and associated with malignant progression and poor clinical prognosis, its clinical significance, correlations with immune infiltration and biological function in ccRCC are still poorly understood. Methods: The gene expression, clinicopathological features, and clinical significance of GTSE1 were analyzed by multiple databases, including TCGA, GEO, TIMER, and UALCAN. Kaplan–Meier survival analysis; Gene set enrichment analysis (GSEA); Gene ontology enrichment (GO); Kyoto Encyclopedia of Genes and Genomes (KEGG); Tumor-infiltrating immune cells and immunomodulators were extracted and analyzed using TCGA ccRCC profiles. Protein-Protein interactions were built using the STRING website. The protein level of GTSE1 in ccRCC patients was detected by immunohistochemistry assay using the ccRCC tissue chip. Finally, MTT assay, colony formation assay, cell flow cytometry analysis, EdU staining assay, wound healing assay, transwell migration, and invasion assay were conducted to assess the biological function of GTSE1 in vitro. Results: GTSE1was overexpressed in ccRCC tissues and cells, and the overexpression of GTSE1 was associated with adverse clinical-pathological factors and poor clinical prognosis. Meanwhile, the functional enrichment analysis indicated that GTSE1 and its co-expressed genes were mainly related to the cell cycle, DNA replication, and immunoreaction such as T cell activation and innate immune response through multiple signaling pathways including the P53 signaling pathway and T cell receptor signaling pathway. Furthermore, we observed a significant relationship between the GTSE1 expression and immune infiltrating levels of different immune cells in ccRCC. Biological functional studies also demonstrated that GTSE1 could promote malignant progression of ccRCC by promoting cell proliferation, cell cycle transition, migration, invasion capacity, and decreasing the sensitivity of ccRCC cells to cisplatin. Conclusion: Our results indicate that GTSE1 serving as a potential oncogene that can promote the malignant progression and cisplatin resistance in ccRCC. Additionally, High GTSE1 expression contributes to an increased level of immune cell infiltration and is associated with a worse prognosis, providing a potential target for tumor therapy in ccRCC.